THU0594-HPR The Determinants of Illness Perceptions in Patients with Acute or Chronic Somatic Diseases: A Mixed-Method Review. (10th June 2014) - Arat, S.; De Cock, D.; Moons, P.; Vandenberghe, J.; Westhovens, R.
Abstract : Background: In order to understand and respond to the difficulties presented by illness, patients construct their own "common sense" cognitive model. This is a way to conceptualize and give meaning to an illness and its consequences, assumed to be influenced by characteristics of both the individual and the particular illness. Objectives: To provide an overview of the available literature on the determinants of illness perceptions in patients with acute or chronic somatic diseases in order to inform us in our planned research studying illness perceptions in rheumatic diseases. Methods: A systematic electronic literature search was conducted using the following databases: Medline (via Pubmed), Embase (via Embase.com), PsycINFO, Cinahl and Invert, complemented by a manual search on reference lists of the included papers. Searches were limited to articles in English, Dutch, French and German published from January 1980 to December 2012. Two authors independently selected studies for inclusion and assessed methodological quality using validated checklists. Results: Thirty-one studies met our inclusion criteria and were hence included in the synthesis (8 qualitative studies, 1 case-control & 22 cohort studies). The determinants found in the papers with qualitative design were culture (n=6) and gender (n=2). The determinants in the quantitative studies were culture (n=8);personal factors such as personality (n=4) and symptom perception (n=1) physical factors such as disability (n=1) and physical functioning (n=1); and illness experience (i.e. personal illness experience (n=3), information source and coping style (n=1) and experiences of disease among relatives and friends (n=1)). The studies, which were conducted in different countries and settings, concerned several diseases. Most but not all studies reported differences in illness perceptions for the determinant culture. In the studies that corrected for educational attainment, no differences were found between different ethnicities. The second determinant, age, revealed that older participants believed genetics to be the cause of their disease. They perceived less control over their illness than younger patients. For personality, patients with type D personality experienced their illness less controllable and were more concerned about their illness than non-type D patients. For the determinant physical functioning, a 6-year longitudinal study about disability in osteoarthritis revealed that disability as result of this disease was predicted by less perceived control and perceptions of stronger consequences at baseline. Illness experience, finally, was related with a stronger belief in control and less severe perceived consequences. Conclusions: Patients who seek care for an acute or chronic illness may have different perceptions and understanding of their disease than does the health care professional.These differences have an influence on the patient-practitioner communication. This review might guide us in our future research on illness perceptions in patients with acute or chronic rheumatic diseases.Research like this is needed to avoid misunderstandings in the patient-practitioner encounter and enables optimal patient care. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3146